(untitled) (SCIENCE TIME JOURNAL, 2026)
The present article investigates the problems that the translators encounter when transferring the unique punctuation system of Fyodor Dostoevsky from Russian into Uzbek. Dostoevsky’s punctuation system was based on his intuitive and highly expressive, mainly through dashes, ellipses, and irregular comma placement, form of intonation. Such difficulties are sailing on language literary translations. The article offers some methodological techniques for these difficulties that are both linguistically accurate and flexibly artistically to be solved.